Das Governance-Dilemma der demokratischen Wirtschaftspolitik - Jörn Kruse (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
As a result of the prevailing governance structure, economic policy in democracies usually suffers from specific deficiencies. Among these are the predominance of distributive over efficiency objectives, the neglect of long-run effects, and the lack of or biased use of expert knowledge in the political decision making process. These deficiencies can be attributed to a 'monopoly of democratic legitimacy' of the politicians and parties, an overloaded democratic delegation, the influence of interest groups, and the short-run incentives in the political process. The focus of this paper is on the reform of the governance structure of economic policy. It is suggested that a 'dual democratic legitimacy' should be introduced. A 'senate' which is independent of the political parties will be directly elected by the people. The senate firstly works as a second chamber in bicameralistic legislation, closely cooperating with consultative expert institutions. Secondly, the senate acts as a principal for any public institution outside of the parliament and the government, appointing the top personnel.
urn:nbn:de:gbv:705-opus-20865
Keywords: D72; D02; 330; Delegation; Politische Institutionen; Zwei-Kammer-Systeme; Senat; Wirtschaftspolitik; Governance-Ansatz; Demokratie; Parlamentarismus; Public Choice; Deutschland